Promenade littéraire: excursões arquiteturais em O Corcunda de Notre Dame - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
It is not new that the interaction between Literature and Architecture is explored by many scholars from a large number of different subject areas. Both practices, each one in its own way, intends to report the spirit of their time, attesting the memories by paper or stone. Their intersection reveals itself fertile by the possibility to see distinct storylines in each one of them. In his debut romance "The Hunchback of Notre Dame", Victor Hugo establishes those interactions on the narrative, exploring architectural and urban spaces, intensifying the effects on the characters. The main objective of this work is to reveal the possible relationship between the "hugoana" ouevre and the architectural space, as those spatial descriptions appearing on the ouevre make possible the narrative's development and, in anon-superficial reading also reveals itself as a theorization device. Ultimately, the ouevre is also taken into account as a theoretical content and critical to the architecture field. In order to lay the foundation of the analysis, it was made a theoretical explanation about the concepts of space, using geographical, philosophic and architecture readings, as much as the literary domain. Straight away, it was indicated the possible relations between literature and the architectural space taking into consideration the Ángel Rama (1998) and Paul Ricoeur (1998) points of view. At the end, it is used the "Topoanálise" method, by Ozíris Borges Filho (2007) in "The Hunchback of Notre Dame" reading. The fact that there is not a single and permanent definition to the idea of space, once that is at the same time concrete and abstract, relative and absolute, make the literature an interesting way of representing it, and, even if in parts, a manner of apprehend it.
Keywords: Literatura; Arquitetura; Topoanálise; Espaço Literário; Literature; Architecture; “Topoanálise”; Literary Space; CNPQ::LINGUISTICA, LETRAS E ARTES